2017
DOI: 10.1055/s-0037-1603817
|View full text |Cite
|
Sign up to set email alerts
|

Women with Symptomatic Preterm Birth Have a Distinct Cervicovaginal Metabolome

Abstract: Objective The objective was to determine if women with symptoms of preterm labor who ultimately have a spontaneous preterm birth (sPTB) have a distinct cervicovaginal (CV) metabolome compared with women who deliver at term. Study Design A nested case–control study of women presenting with symptoms of preterm labor was performed. CV fluid was collected from women between 22 and 336/7 weeks' gestation. The CV metabolome was compared between women with sPTB (n = 20) and women who delivered at term (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The cervicovaginal space is metabolically active in pregnancy, and microbiota in this ecosystem can produce, modify, and degrade metabolites 29 31 . Our group previously identified a cervicovaginal metabolomic signature in pregnancy, including distinct biochemicals associated with sPTB 29 , 30 . While these early studies suggest that metabolites may provide a lens into mechanisms underlying premature cervical remodeling, they did not incorporate data on microbiota composition.…”
Section: Introductionmentioning
confidence: 99%
“…The cervicovaginal space is metabolically active in pregnancy, and microbiota in this ecosystem can produce, modify, and degrade metabolites 29 31 . Our group previously identified a cervicovaginal metabolomic signature in pregnancy, including distinct biochemicals associated with sPTB 29 , 30 . While these early studies suggest that metabolites may provide a lens into mechanisms underlying premature cervical remodeling, they did not incorporate data on microbiota composition.…”
Section: Introductionmentioning
confidence: 99%
“…The cervix has several critical functions including (1) maintenance of the integrity of the cervical epithelial barrier that lines the cervical lumen and acts to prevent microbial invasion and infection and (2) appropriate timing of cervical remodeling to prepare for delivery. Previous studies by our group and others have shown that many factors can promote a breakdown in the cervical epithelial barrier and initiate cervical remodeling through alterations in inflammation and infection ( Nold et al, 2012 ), microRNAs (miRNAs) ( Anton et al, 2017 ), biomechanical properties of the cervix ( Yoshida et al, 2016 ; Barnum et al, 2017 ), and the CV metabolome ( Ghartey et al, 2015 , 2017 ) and microbiome ( Romero et al, 2014a ; Stout et al, 2017 ). Differentially expressed miRNAs in the CV space are associated with PTB ( Elovitz et al, 2014 ), short gestation ( Sanders et al, 2015 ), and disruption of the cervical epithelial barrier ( Anton et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ghartey et al (2015; found that women with symptoms of preterm birth and eventually spontaneous preterm birth (sPTB) have significant changes in cervicovaginal metabolites. Lipid metabolism and carbohydrate metabolism in the cervicovaginal secretions of women who deliver prematurely are significantly upregulated, and peptide levels are significantly reduced (Ghartey et al, 2015;Ghartey et al, 2017). Upregulation of lipid and carbohydrate pathways is associated with positive energy utilization and may be related to early cervical remodeling and sPTB microbiota utilization (Ghartey et al, 2015;Ghartey et al, 2017).…”
Section: Preterm Birthmentioning
confidence: 99%
“…Lipid metabolism and carbohydrate metabolism in the cervicovaginal secretions of women who deliver prematurely are significantly upregulated, and peptide levels are significantly reduced (Ghartey et al, 2015;Ghartey et al, 2017). Upregulation of lipid and carbohydrate pathways is associated with positive energy utilization and may be related to early cervical remodeling and sPTB microbiota utilization (Ghartey et al, 2015;Ghartey et al, 2017). A decrease in dipeptides may reflect the decreased level of proteolysis in women who deliver prematurely and changes in the activities of proteases and are associated with asymptomatic sPTB (Ghartey et al, 2015).…”
Section: Preterm Birthmentioning
confidence: 99%